Changes in the accuracy of administrative data for the detection of surgical site infections. (17th September 2021) - Bucher, Brian T.; Yang, Meng; Arndorfer, Julie; Frame, Cherie; Orton, Jan; Samore, Matthew H.; Dascomb, Kristin K.
Abstract: We performed a retrospective analysis of the changes in accuracy of International Classification of Diseases, Clinical Modification (ICD-CM) diagnosis codes for colectomy and hysterectomy surgical site infection surveillance. After the transition from ICD-CM ninth edition to tenth edition codes, there was no significant change in the accuracy of these codes for SSI surveillance.